Mode I interlaminar fracture toughness of carbon‐epoxy coupons with embedded ceramic sensors. Issue 6 (9th October 2017) - Torres, Mauricio; Tellez, Ricardo A.; Hernández, Hilario; Camps, Thierry
Abstract: This study analyses the mechanical and crack growth behavior of woven carbon fiber reinforced plastics (CPRF) with embedded ceramic sensors. The material studied here is 3K‐70‐P carbon fiber plain weave with EPOLAM 2015® epoxy resin. The composite is manufactured with vacuum bagging procedure. Later on, the composite Mode I interlaminar fracture toughness ( G IC ) is calculated by means of double cantilever beam tests (DCB) for two layout configurations [0/90] and [±45] with and without embedded sensors. Results give an initial approach of the fracture behavior of an instrumented composite facing an interlaminar crack. The interlaminar fracture toughness for the instrumented specimens is lower compared to the noninstrumented coupons. The presence of the sensor and its wire connection has a considerable impact on the damage tolerance of the woven composite, where the sensors surroundings seem to be the more likely region to be affected by an interlaminar fracture.